Consequences of aneuploidy in sickness and in health. (June 2016) - Rutledge, Samuel D; Cimini, Daniela
Abstract : A link between aneuploidy and miscarriage or cancer in humans has been known for a long time. However, only in recent years the development of experimental models of whole-chromosome aneuploidy has allowed investigators to take a closer look at how aneuploidy affects individual cells. Collectively, recent studies using these models have shown that aneuploidy induces transcriptomic and proteomic changes, chromosomal instability, and adaptation. In this article, we discuss the findings from these recent studies and present current and emerging models on how aneuploidy may be deleterious in certain contexts, but beneficial in others.